Tracing the cultural heritage of Mahakam Ulu: Towards a strategy for cultural advancement - Emilda Kuspraningrum; Rika Erawati; Sukapti Sukapti; Febri Noor Hediati; Sonny Sudiar; Mahendra Putra Kurnia; Kamilah Dwi Kurniawati; Rofiqul Ulum (Priviet Social Sciences Journal, 2026)
This study aims to explore the potential, challenges, and efforts that can be undertaken to advance the culture of Mahakam Ulu Regency, East Kalimantan. The regency possesses a diverse cultural heritage, particularly from the Dayak community and its various subgroups, which is reflected in cultural advancement objects such as oral traditions, manuscripts, rites, traditional knowledge, local technology, arts, language, folk games, traditional sports, and cultural heritage sites. This study employs a descriptive qualitative approach through document analysis, involving an examination of various written sources, including government documents, and academic publications. The findings indicate that strategies to preserve the cultural diversity of Mahakam Ulu must be implemented comprehensively and collaboratively, especially amid the influences of modernization, the lack of cultural practitioner regeneration, and limited human resources and preservation funds. Efforts to advance culture have been carried out through protection, development, utilization, and fostering, integrated into local tourism development